2010
DOI: 10.1063/1.3428433
|View full text |Cite
|
Sign up to set email alerts
|

Diodes with breakdown voltages enhanced by the metal-insulator transition of LaAlO3–SrTiO3 interfaces

Abstract: Using the metal-insulator transition that takes place as a function of carrier density at the LaAlO3-SrTiO3 interface, oxide diodes have been fabricated with room-temperature breakdown voltages of up to 200 V. With applied voltage, the capacitance of the diodes changes by a factor of 150. The diodes are robust and operate at temperatures up to 270 C.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 9 publications
6
23
0
Order By: Relevance
“…3(a), the highly resistive initial resistance state (IRS) of the Pt/LAO/STO heterojunction exhibits significant rectification at room temperature in a voltage sweep from À4 to þ4 V, indicating that the LAO layer retains its expected insulating characteristics. The rectifying behavior is similar to a recent report on a diode based on the LAO/STO interface with Au electrodes [40]. However, in our devices, this pristine state can be transformed into a switchable state using a simple reverse voltage sweep to À4 V. In the regime of negative bias, notable current fluctuations are observed that prelude the stable RS operations with bipolar switching I-V loops.…”
Section: Resultssupporting
confidence: 89%
“…3(a), the highly resistive initial resistance state (IRS) of the Pt/LAO/STO heterojunction exhibits significant rectification at room temperature in a voltage sweep from À4 to þ4 V, indicating that the LAO layer retains its expected insulating characteristics. The rectifying behavior is similar to a recent report on a diode based on the LAO/STO interface with Au electrodes [40]. However, in our devices, this pristine state can be transformed into a switchable state using a simple reverse voltage sweep to À4 V. In the regime of negative bias, notable current fluctuations are observed that prelude the stable RS operations with bipolar switching I-V loops.…”
Section: Resultssupporting
confidence: 89%
“…6 Furthermore, this electric-field controlled interfacial metal-insulator ͑MI͒ transition can also be realized at nanometer scales by means of a conducting atomic force microscopy ͑CAFM͒ probe. 7 These findings show application potentials in oxide electronic devices, 8,9 however, their underlying mechanisms are also not clarified unambiguously. In this letter, besides the electric-field controlled interfacial MI transition at d =3 uc in air, a reproducible resistance switching of the interfacial conductance is observed for d Ն 3 uc samples in a vacuum environment, which is proposed to originate from the modulation of oxygen ion transfer in STO by external electric field near the interface.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] However, no consensus on its origin has been achieved. 3 The polar catastrophe induced electronic reconstruction, 1,2 the oxygen vacancies dominated conduction, 4 or the extrinsic doping by La-interdiffusion at interface, 5 all can explain the conducting behavior.…”
mentioning
confidence: 99%
“…The electron density at the interface can be controlled using a number of techniques including back-gating 22 , top-gating 23 , polar adsorbates 24 or via nanoscale control using conductive atomic force microscopy (AFM) lithography 25 .…”
mentioning
confidence: 99%